Desenvolvimento de procedimento analítico de pré – concentração de Cr (III) em fase sólida empregando ponteiras descartáveis em matrizes aquosas - Silva, Weida Rodrigues (2019)
The solid phase extraction technique (SPE) is widely used in the extraction and preconcentration stages of the most analytical species and it can also be applied in the removal of heavy metals. The SPE can be adapted for the use of disposable tips, known as DPX (disposable pipette extraction) method. In this study, a procedure was developed for preconcentration of Cr (III), using a bark of coffee as adsorbent and DPX and determination by flame atomic absorption spectrometry (F AAS). Preliminary tests were performed to choose the treatment of adsorbent (in natura, HCl, NaOH and hexane). Infrared spectrometry, thermogravimetric analysis, scanning electron microscopy, and dispersive energy spectroscopy techniques were used to characterize the adsorvent material. The kinetic study of the adsorption process of Cr (III) by the adsorbent showed that the adsorption equilibrium was reached in 10 minutes, with removal of up to 50% using 25 mg of adsorbent. The kinetic models of pseudo-first order and pseudo-second order were used to evaluate experimental data. Langmuir, and Freundlich models were used to understand the adsorption mechanism. For the preconcentration of Cr (III) by DPX, the steps such as conditioning the extractive phase, sample aspiration, air aspiration, sample dispensing and elution were optimized to establish the best equilibrium condition. Thus, 1 mL of deionized water for conditioning, 4 mL of solution, 25 mg of solid phase, 2 cycles of extraction, 200 μL of HCl in 1 elution cycle were the optimized conditions. The study showed the viability of the use of the bark of in natura coffee for Cr (III) extraction and preconcentration. On optimized conditions, the calibration curve was linear in the range of 0.02 - 1.00 mg L-1. The limits of detection and quantification achieved were 0.0062 and 0.0207 mg L-1 respectively, obtaining an enrichment factor of 11 and the value corresponding to the relative standard deviation (D.P.R.) for 10 replicates were below 5%. The accuracy of the method was tested using certified material. Recovery values were obtained between 103 to 104% for fortified samples. The method was applied satisfactorily for the determination of Cr (III) in water samples. The study showed the feasibility of using the in natura coffee film for Cr (III) extraction and preconcentration.